2011
DOI: 10.2298/vsp1106476t
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hysteroscopic examination on the outcome of in vitro fertilization

Abstract: Considering the results of this study we could conclude that hysteroscopy, as a routine examination, should be performed before the first IVF-ET cycle in all patients thereby reducing the failures and then the costs of IVF-ET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 15 publications
0
2
1
Order By: Relevance
“…In their meta-analyses, Pundir and El-Toukhy found the proof of the hysteroscopy benefit prior to the first IVF cycle, proving a higher pregnancy rate with women who underwent hysteroscopy procedure [4]. One more research with 480 patients also showed higher pregnancy rates when hysteroscopy was performed before the first IVF [14]. Our study did not provide information about hysteroscopy itself influencing statistically better IVF outcome results.…”
Section: Discussioncontrasting
confidence: 54%
“…In their meta-analyses, Pundir and El-Toukhy found the proof of the hysteroscopy benefit prior to the first IVF cycle, proving a higher pregnancy rate with women who underwent hysteroscopy procedure [4]. One more research with 480 patients also showed higher pregnancy rates when hysteroscopy was performed before the first IVF [14]. Our study did not provide information about hysteroscopy itself influencing statistically better IVF outcome results.…”
Section: Discussioncontrasting
confidence: 54%
“…2d) was removed from the stomach by surgical intervention. Surgical solution for gastric trichobezoar in children has been mentioned in numerous papers as a method of choice [8,[14][15][16]].…”
Section: Discussionmentioning
confidence: 99%
“…The idea of performing hysteroscopy prior to every IVF procedure was greatly favored for two reasons: due to high frequency of uterus cavum pathological states (10%-60%) and the influence of hysteroscopy itself on the better IVF outcome 1,2 .…”
Section: Introductionmentioning
confidence: 99%